In-Silico Study of Diphenhydramine and Orphenadrine Binding Affinities to H1 and NMDA Receptors: Implications for Pharmacological Effects - Utama, Andrea Dhieta; Widiyanto, Azura Luna; E, Ervin; Elvina, Lia; Cahya, Rachel Josephine; Feliecia, Silvania; Putri, Stevanie (Indonesian Journal of Life Sciences, 2025)
Diphenhydramine and orphenadrine are oral drugs designed to possess different functional groups that affect H1 and NMDA receptors, although for different purposes. This study compares their binding affinities with the two receptors to investigate whether it influences the differing pharmacological effects exerted. This could help better understand the mechanisms, benefits, and risks of the drugs. The physicochemical properties were analyzed using Swiss-ADME, while the binding affinities were tested by molecular docking with PyRx. Lastly, visualization and analysis were done using the BIOVIA Drug Discovery Studio. The result suggests that both drugs have the same affinity for H1 receptors, however, orphenadrine has a slightly higher affinity to NMDA than diphenhydramine. This finding suggests that the binding ability and affinity of orphenadrine to NMDA is the factor of its pharmacological effect difference compared to diphenhydramine. Moreover, the difference in the functional group possessed by the two drugs will make a difference in their absorption and distribution.